Postoperative autovaccinotherapy for patients with gastric cancer and expression of some proteins in tumor tissue - Bazas, V.M.; Lukyanova, N.Yu.; Lisovenko, G.S.; Rozumiy, D.O.; Potebnya, G.P. (Experimental Oncology, 2009)
Aim: To study the efficacy of autovaccine in the treatment of gastric cancer and significance of molecular factors having prognostic values for disease outcome to evaluate its efficacy in clinical setting. Patients and Methods: 150 patients with histologically proven adenocarcinoma of the stomach of stages II, III or IV were enrolled into study. 86 patients have been treated with autovaccine (AV) after operation. Expression of p53, Bcl-2, receptors of tyrosine kinase, vascular endothelial growth factor (VEGF), Е-cadherin, α-catenin and β-catenin was determined in paraffin embedded tumor samples by means of immunohistochemical method with the use of respective monoclonal antibodies. Results: It was shown that application of AV has resulted in the increase of 3-year overall survival of patients having stage III of disease by more than 30%, but those having stage IV — only around 14%. The increase of 3-year overall survival of patients with metastases in lymph nodes (N1–2) was observed also in more than 30%. It has been suggested the optimal phenotype for vaccine application: р53(+), EGFR(+), HER-2 neu (+), β-catenin (+), VEGF(+) and Bcl-2(+) with no dependence on E-cadherin and α-catenin presence. Conclusion: It was determined that the best effect of AV application is observed in patients with category Т3–4, poorly-differentiated tumors, metastases in lymph nodes (N1–2), but without distant metastases (М0). Gastric cancer patients with p53, EGFR, HER-2/neu, β-catenin, VEGF and Bcl-2-positive tumors are the favorable group for the treatment with AV in the adjuvant regime.